2007
DOI: 10.1124/jpet.107.134593
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Kinetics and Metabolism of Dichloroacetate: Possible Relevance to Toxicity

Abstract: Dichloroacetate (DCA) is an investigational drug for certain metabolic diseases. It is biotransformed principally by the -1 family isoform of glutathione transferase (GSTz1), also known as maleylacetoacetate isomerase (MAAI), which catalyzes the penultimate step in tyrosine catabolism. DCA causes a reversible peripheral neuropathy in several species, including humans. However, recent clinical trials indicate that adults are considerably more susceptible to this adverse effect than children. We evaluated the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 20 publications
5
83
1
Order By: Relevance
“…DCA is already established in clinical practice. The Cmax value of DCA in adults following 6 months of continuous treatment (oral doses of 25 mg/kg/day) was 53±18 µg/ml (0.35±0.12 mM) (18). Patients were safely treated chronically with DCA at the maximum dose of 50 mg/kg/day (19).…”
Section: Discussionmentioning
confidence: 99%
“…DCA is already established in clinical practice. The Cmax value of DCA in adults following 6 months of continuous treatment (oral doses of 25 mg/kg/day) was 53±18 µg/ml (0.35±0.12 mM) (18). Patients were safely treated chronically with DCA at the maximum dose of 50 mg/kg/day (19).…”
Section: Discussionmentioning
confidence: 99%
“…Human studies showed no differences in single-dose DCA pharmacokinetics between children younger than 7 years and adults (mean age, 24 years) (Shroads et al, 2008(Shroads et al, , 2011. The initial elimination half-life was 2.5 Ϯ 0.4 h (mean Ϯ S.D.)…”
Section: Et Almentioning
confidence: 93%
“…In contrast, children with heterogeneous causes of congenital lactic acidosis showed no worsening of hepatotoxicity or neurotoxicity even after chronic DCA treatment . Examination of DCA plasma kinetics revealed similar clearance and other indices between children (age, 2.2-7.1 years at entry; mean age Ϯ S.D., 5.2 Ϯ 1.8; n ϭ 5) and older individuals (age, 14.0 -33.9 at entry; mean age Ϯ S.D., 23.6 Ϯ 10.0; n ϭ 4) after their initial doses, whereas a striking age-dependent decrease in DCA clearance was observed at the end of 6 months of treatment (Shroads et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…GSTZ1 is the only GST known to metabolize DCA. A trace amount of DCA can also be reductively dechlorinated to monochloroacetate in the blood (Shroads et al, 2008). In vivo exposure to DCA causes a dose-and duration-dependent reduction in hepatic GSTZ1 expression and activity (Cornett et al, 1999;Ammini et al, 2003).…”
Section: Introductionmentioning
confidence: 99%